2014
DOI: 10.1016/j.nbd.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 mutations cause mitochondrial DNA damage in iPSC-derived neural cells from Parkinson's disease patients: Reversal by gene correction

Abstract: Parkinson’s disease associated mutations in leucine rich repeat kinase 2 (LRRK2) impair mitochondrial function and increase the vulnerability of induced pluripotent stem cell (iPSC)-derived neural cells from patients to oxidative stress. Since mitochondrial DNA (mtDNA) damage can compromise mitochondrial function, we examined whether LRRK2 mutations can induce damage to the mitochondrial genome. We found greater levels of mtDNA damage in iPSC-derived neural cells from patients carrying homozygous or heterozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
209
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(218 citation statements)
references
References 23 publications
8
209
1
Order By: Relevance
“…Dopamine neurons derived from pluripotent stem cells from R1441C mutation carriers revealed mitochondrial pathology presumably due to mitochondrial DNA damage, which could be rescued pharmacologically or by gene correction [153,154]. Similar effects on mitochondrial function have been seen in G2019S fibroblasts [155].…”
Section: Effects Of Lrrk2 On Cellular Phenotypes and Physiologymentioning
confidence: 64%
“…Dopamine neurons derived from pluripotent stem cells from R1441C mutation carriers revealed mitochondrial pathology presumably due to mitochondrial DNA damage, which could be rescued pharmacologically or by gene correction [153,154]. Similar effects on mitochondrial function have been seen in G2019S fibroblasts [155].…”
Section: Effects Of Lrrk2 On Cellular Phenotypes and Physiologymentioning
confidence: 64%
“…4G). Thus far, studies have focused on PD-iPSCs carrying LRRK2 mutations (Cooper et al, 2012;Liu et al, 2012a;Nguyen et al, 2011;Reinhardt et al, 2013;Sanchez-Danes et al, 2012b;Sanders et al, 2014), SNCA triplication Devine et al, 2011), SNCA A53T mutation (Ryan et al, 2013;Soldner et al, 2011), PINK mutations (Cooper et al, 2012;Seibler et al, 2011) or GBA1 heterozygosity (Mazzulli et al, 2011;Schöndorf et al, 2014). Most of these studies relied on protocols with suboptimal WNT/β-catenin activation, which do not give rise to correctly specified mDA neurons.…”
Section: Box 4 Generation Of Mda Cells For In Vitro Pd Modelingmentioning
confidence: 99%
“…Gene editing technologies, such as zinc-finger nucleases, TALENS or the CRISPR/Cas9 system, are currently being used to correct or introduce PD mutations and control for the genetic background of PD-iPSCs (Chung et al, 2013;Liu et al, 2012a;Reinhardt et al, 2013;Ryan et al, 2013;Sanders et al, 2014;Schöndorf et al, 2014;Soldner et al, 2011). These methods can be used to introduce/correct multiple mutations and examine epistatic interactions between PD genes, allowing more complete iPSC models in which several features of PD are simultaneously examined.…”
Section: Box 4 Generation Of Mda Cells For In Vitro Pd Modelingmentioning
confidence: 99%
“…Indeed, such iPSC-based disease models are rapidly developing into a key platform for drug discovery and preclinical testing of candidate compounds (Lee et al, 2009(Lee et al, , 2012aMerkle and Eggan, 2013;Wainger et al, 2014). In the case of PD, recent studies have demonstrated that neurons derived from patient-specific iPSCs could successfully reproduce several disease-related phenotypes such as increased α-synuclein levels, mitochondrial dysfunction and hypersensitivity to toxins such as compounds that trigger mitochondrial stress or ROS (Byers et al, 2011;Devine et al, 2011;Seibler et al, 2011;Soldner et al, 2011;Cooper et al, 2012;Imaizumi et al, 2012;Liu et al, 2012;Sánchez-Danés et al, 2012;Miller et al, 2013;Reinhardt et al, 2013;Su and Qi, 2013;Sanders et al, 2014;Woodard et al, 2014). Most of these models showed evidence of biochemical changes that are directly dependent on the disease-specific genetic defects (Fig.…”
Section: Late-onset Disease Modeling: Insights From Parkinson's Diseasementioning
confidence: 99%